Correlation of Low CD4+ Counts with High Dental Caries Prevalence in Children Living with Perinatal HIV/AIDS Undergoing Antiretroviral Therapy - Alexander Patera Nugraha (Association of Support to Oral Health Research (APESB), 2019)
Objective:To investigate the correlation Cluster of Differentiation 4+(CD4+) counts with a high prevalence of dental caries in Children Living with Perinatal Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (CLWPHA). Material and Methods:An analytical observational research with a cross-sectional design was conducted at Tertiary General Hospital, Surabaya, Indonesia. Randomized total sampling consisted of 29 CLWPHA 1-12 years old at outpatient ward Infectious Disease Intermediate Unit (UPIPI) Tertiary General Hospital Doctor Soetomo Surabaya. Demographic details and recent CD4+counts obtained from medical records. Decayed, missing, filled teeth (dmft) in primary teeth and DMFT in permanent teeth index were used. Pearson's and Spearman's Correlation test (p<0.05) were performed. Results:Dental caries prevalence was 86.2%; meanwhile, the dmft/DMFT index score found were high (8.2 / 6.3). CD4+count and caries showed significant correlation (r=-0.394, p<0.05). Tooth brushing frequency with caries showed a significant correlation (r=-0.419, p<0.05). Antiretroviral (ARV) therapy and caries showed an insignificant negative correlation (p<0.05). Conclusion:The high prevalence of dental caries in CLWPHA correlated with low CD4+counts.